2011
DOI: 10.1016/j.apsusc.2010.11.104
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of chitosan/hydroxyapatite membranes coated with hydroxycarbonate apatite for guided tissue regeneration purposes

Abstract: Chitosan, which is a non-toxic, biodegradable and biocompatible biopolymer, has been widely researched for several applications in the field of biomaterials. Calcium phosphate ceramics stand out among the so-called bioceramics for their absence of local or systemic toxicity, their non-response to foreign bodies or inflammations, and their apparent ability to bond to the host tissue. Hydroxyapatite (HA) is one of the most important bioceramics because it is the main component of the mineral phase of bone. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 13 publications
(14 reference statements)
1
23
0
Order By: Relevance
“…This method consists initially in an alkaline treatment, in which the substrate is submerged in a 5M NaOH solution at 60ºC for 24 hours, to produce active sites on the metal surface, in order to favor hydroxyapatite precipitation 5,19 . Subsequently, the substrate was subjected to a heat treatment at 600ºC for one hour and cooled at room temperature, to eliminate the hydrated phase and form a stable layer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method consists initially in an alkaline treatment, in which the substrate is submerged in a 5M NaOH solution at 60ºC for 24 hours, to produce active sites on the metal surface, in order to favor hydroxyapatite precipitation 5,19 . Subsequently, the substrate was subjected to a heat treatment at 600ºC for one hour and cooled at room temperature, to eliminate the hydrated phase and form a stable layer.…”
Section: Methodsmentioning
confidence: 99%
“…Titanium and its alloys are prominent for presenting biocompatibility, high resistance to corrosion and a relatively low density, becoming important materials for research in the field of Biomedicine [1][2][3][4][5] . Nevertheless, results confirm that the bioactive materials in the surface of the implant favor osseointegration time.…”
Section: Introductionmentioning
confidence: 99%
“…The coating or incorporation of calcium salts such as calcium silicate [48] or calcium carbonate (CaCO3) [50], or bioactive glass [46,49], have contributed to improve the osteoconductive and osteoinductive properties of GBR membranes. Fraga et al [48] produced a chitosan membrane coated with calcium silicate that showed to induce the formation of a low crystallinity hydroxyapatite layer similar to the human bone in vitro, when immersed in a SBF solution. A chitosan membrane combined with bioactive glass was developed by Mota et al [46].…”
Section: Alginate and Chitosan Based Barriersmentioning
confidence: 99%
“…Other biomaterials used for tissue engineering purposes have been tested in the development of membranes for GTR applications. Materials such as alginate, chitosan, polycaprolactone or poly (trimethylene carbonate) have been used in recent studies [41][42][43][44][45][46][47][48][49][50].…”
Section: Collagenmentioning
confidence: 99%
“…46 To enhance the osteoconductivity of implants, many methods, such as plasma spraying, 8,15 sol-gel process, 45 electrochemical deposition 9 and simulated body fluid (SBF) treatments, 2,11,31,44 have been proposed to produce a calcium phosphate layer on implant surfaces. Compared with the other processes, SBF treatments create a uniform calcium phosphate layer under mild and ecofriendly conditions.…”
Section: Introductionmentioning
confidence: 99%